Colaboration to development nursing in africans countries - Oguisso, Taka (Revista da Escola de Enfermagem da USP, 1993)
The support offered by the ICN to the african countries of portuguese language, is described in this paper. The countries that participated of the ICN' Project were Angola, Cabo Verde, Guiné-Bissau, Moçambique. São Tomé and Principe. The purposes of the project arc-analyse development of nursing in these countries; identify the needs of the nurses of the these countries; to evaluate the health systems and work to introduce the nurse in these systems: to identify the strughts and issues of the nursing associations; to promote the relationship among nurses and to estabilish plan to reinforce the national Nursing Association. We don't think that nursing is ready and well structured now, but this Project will be the first step in this direction. We have results an had some exemple of this is affiliation to the ICN of some African countries that have been made.